INSTITUTIONAL CAPACITY AND STUDENTS’ ACADEMIC PERFORMANCE IN OYO STATE SECONDARY SCHOOLS - Azeez, Nurudeen Oluwadare; Adefabi, Rasaq Adetunji; Ajasa, Folorunso Adekemi (African Journal of Education and Practice, 2020)
Purpose: This study investigated the relationship which exists between institutional capacity and students' academic performance in Oyo State secondary schools. Methodology: The researcher adopted descriptive research design of survey type. The population for the study consisted of all teachers in all the 324 public secondary schools in Oyo State. Stratified random sampling and proportional sampling techniques was used to select 15 local Government Areas out of 33 Local Government Areas that form the three Senatorial Districts of the state. Forty public secondary schools out of 112 in the sampled Local Governments. Four hundred and fifteen respondents selected out of 1,230 teachers in all the selected schools. A researchers' self-designed instrument titled "Institutional Capacity Questionnaire" (ICQ) was adopted to elicit information from the respondents. The instrument was validated and tested for reliability. A reliability coefficient of .72 was obtained. The instrument was administered by the researcher and some trained research assistants. Hypotheses formulated were tested using Pearson product-moment correlation statistics at 0.05 level of significance. The coded data were analyzed using inferential statistics of Pearson product-moment correlation statistics at 0.05 level of significance and 413 degrees of freedom. Findings: Main finding of this study revealed that there was significant relationship between institutional capacity and students' academic performance in Oyo State secondary schools. Other findings of the study revealed that there was significant relationship between school population and students' academic performance in Oyo State secondary; there was significant relationship between classrooms and students' academic performance in Oyo State secondary schools; there was significant relationship between teacher-students ratio in Oyo State secondary schools. Unique contribution to theory, practice and policy: It was recommended among others that public secondary schools in the State should admit students according to what their school capacity can carry, and that the government, Parents-Teacher Association (P.T.A.) and other stakeholders in education should help to build and provide more classrooms, appoint more qualified teachers that will cater for the school population.